Demystifying the Sublime City in Paul Auster’s In the Country of Last Things - Hasine Sen Karadeniz (American Studies in Scandinavia, 2018)
The present study discusses the demystification of the urban sublime in Paul Auster’s In the Country of Last Things. It sets the term in a US context and discusses its specificity through the examination of the relationship of the urban sublime with a pair of interrelated concepts: the technological sublime and the consumer’s sublime. This theoretical preview verifies that the architectural and technological structure of the city has been subordinated to the logics of capitalist economy. The paper evaluates Auster’s novel as a critique of the deferential elevation of the urban landscape through its reduction to the dystopian images of garbage and waste; through the reversal of the object of the sublime from the infinitely large to the infinitely small, from the urban to the natural; and through the subversion of the power dynamics attributed to the skyscraper, the central emblem of the urban sublime. It asserts that the foregrounding of the act of falling, set against the pronounced upward orientation of the urban landscape, defines the city as an inherently lethal area capable of arousing a single passion linked to the notion of the sublime—terror.